2014
DOI: 10.1002/zoo.21193
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the prevalence of exploratory behavior in captive cheetahs (Acinonyx jubatus)

Abstract: Exploratory behavior in the wild is fundamentally linked to an animal's survival and natural life history. The ability to gather information about their environment, establish territories, assert dominance, communicate information regarding reproductive status and locate mates are closely associated with a range of exploratory behaviors. Understanding how these behaviors are performed within the captive setting is crucial in order to create a captive environment in which these behaviors can be expressed, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Yet, cheetahs may not experience stress principally because they are kept in captivity, but when they are kept in close contact with conspecifics [Clauss et al, ; Troxell‐Smith and Miller, ]. Close proximity to conspecifics was suggested as the cause of reproductive failure [Jurke et al, ] and cheetahs kept in groups show more hormonal and behavioral abnormalities than those kept individually [Quirke and O'Riordan, , ]. Managing diseases such as gastritis and myocardial fibrosis (and possibly glomerulosclerosis and systemic amyloidosis) in captive cheetahs likely therefore depends on prevention, early detection, and alleviation of these stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, cheetahs may not experience stress principally because they are kept in captivity, but when they are kept in close contact with conspecifics [Clauss et al, ; Troxell‐Smith and Miller, ]. Close proximity to conspecifics was suggested as the cause of reproductive failure [Jurke et al, ] and cheetahs kept in groups show more hormonal and behavioral abnormalities than those kept individually [Quirke and O'Riordan, , ]. Managing diseases such as gastritis and myocardial fibrosis (and possibly glomerulosclerosis and systemic amyloidosis) in captive cheetahs likely therefore depends on prevention, early detection, and alleviation of these stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Giving the animals themselves the option to move between exhibits has many benefits such as increasing available space, stimulating natural behavior, and empowering animal choice. Several studies have suggested that giving animals choice over their environment is critical to achieving good welfare (Johnson & Langton, 2021; Lukas et al, 2003; Owen et al, 2005; Quirke & O'Riordan, 2015; Ross, 2011). Providing options to seek and freely enter multiple locations within a larger exhibit can serve as a form of enrichment that enhances welfare (Mench, 1998; Ross, 2006; Young, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of intrinsic enrichment, such as new objects and scents into the captive environment, can increase exploration and stimulate territorial behaviors, such as scent marking, while also improving psychological well‐being (Quirke & O'Riordan, ; Tarou & Bashaw, ; Wells, ; Wells & Egli, ). Wells and Egli () introduced three different types of odors to black‐footed cats ( Felis nigripes ) and observed an increase in activity and exploration.…”
Section: Introductionmentioning
confidence: 99%